Green synthesis of Cu-SSZ-13 zeolite by seed-assisted route for effective reduction of nitric oxide. (1st November 2019) - Xin-yan, Zhang; Ting-ting, Dou; Yao, Wang; Jing-yue, Yang; Xue, Wang; Yan-yan, Guo; Qun, Shen; Xin, Zhang; Shao-qing, Zhang
Abstracts: One of the main technologies to solve NOx pollution in vehicle exhaust is selective catalytic reduction. The Cu loaded SSZ-13 zeolites catalyst material is one of the most attractive catalytic materials used in this technology. Moreover, green synthesis route of copper based SSZ-13 without or less organic template agent using in order to promote its practical industrial application is a promising and meaningful research hotpot. In this paper, low-cost Cu-SSZ-13 zeolites were successfully synthesized by seed orientation method and evaluated for its catalytic properties of NOx reduction. The crystallization conditions and crystallization mechanism were systematically investigated. The results show that the amount of seed, the ratio of Si to Al, crystallization temperature, crystallization time and seed state (calcined or unroasted) all have effect on the synthesis of molecular sieve. With 10–20% SSZ-13 seeds adding, SSZ-13 zeolites at Si/Al ratio of 17.5–25 can be successfully prepared for hydrothermal treatment at 100 °C–120 °C for 2–6 days. And the optimum conditions for the synthesis of SSZ-13 zeolites by seed orientation method are as follows: using silica sol, aluminum sulfate, sodium hydroxide and deionized water as raw materials, and mixing them with the molar ratio of SiO2 :Al2 O3 :Na2 O:H2 O = 40:1:16:900; taking the 15% unroasted SSZ-13 as seed, high purity SSZ-13 molecular sieve can be obtained by crystallization at 100 °C for 4 days. The results of crystallization mechanism investigations show that the synthesis of zeolites by seed-guided method is in accordance with the "core-shell" growth mechanism that the Si source and Al source continue to grow on the seed substrate in the Crystallization process. The copper loaded SSZ-13 zeolites by ion exchange method showed good selective catalytic reduction performance of NOx, which is compared to the activity of Cu-SSZ-13 zeolites prepared using traditional organic template agent. Thus, the low-cost seed-assisted, organic template agent-free synthesis of Cu-SSZ-13 zeolite has very promising application prospect in future NOx purification in vehicle exhaust. Graphical abstract: Image 10988 Highlights: Green Cu-SSZ-13seed was successfully synthesized by seed orientation method. Cu-SSZ-13seed shows excellent NOx removal performance and promising applications. The optimum synthesis conditions and crystallization mechanism were investigated. The seed-oriented synthesis of SSZ-13 follows a core-shell growth mechanism.